PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN GUIDED INQUIRY LEARNING PADA MATERI ENERGI DALAM SISTEM KEHIDUPAN - Septiara, Salsabila; Nurita, Tutut (PENSA E-JURNAL: PENDIDIKAN SAINS, 2021)
This study aims to describe the improvement of students’ critical thinking skills by applying guided inquiry learning model. This research used pre-experimental design with One-Group Pre-test-Post-test design type. This study was conducted at JHS 1 Sidoarjo because of the students’ critical thinking skills were low and guided inquiry learning model has never been applied. The method of this research is descriptive quantitative. Observation of guided inquiry implementation, critical thinking skills test and student response questionnaires were data collection methods that used in this study. The research results obtained data: (1) The implementation of guided inquiry in 7F and 7G obtained score percentage above 81% with excellent category. (2) There was an increase in the percentage of achievement from each indicator of critical thinking skills. An increase of critical thinking skills in 7F and 7G were 0.75 and 0.82 with high category based on n-gain score. (3) The results of the response of students showed a positive response as evidenced by the results of questionnaire percentage 93% and 96% with excellent category. Based on these results, it can be concluded that the guided inquiry learning model can improve students’ critical thinking skills on energy in life system topic.